Corporate Social Responsibility and Market-Adjusted Stock Returns: An Asian Perspective - Mutuc, Eugene Burgos (Animo Repository, 2019)
This study investigates the short-run and long-run effects of corporate social responsibility (CSR) on firms’ financial performance through market-adjusted stock returns from one year to three years holding periods. We analyze the year 2015 CSR data of 958 publicly-listed companies from 11 countries in Asia. This study also reflects on the disaggregated effects of three pillars of CSR, namely: environment, social, and governance. We conjecture that the trade-off does not exist between building corporate citizenship and financial performance, in light of increasing attention of CSR among Asian countries. We also examine the phenomenon in the contexts of country and sector levels. Our main findings reveal that CSR has a cumulative effect, which reinforces better financial performance in the future. This study also shows mixed evidence regarding the disaggregated effect of CSR pillars. Moreover, we find that the impact of CSR and its pillars on market-adjusted stock returns vary per country and per sector. We argue that our results are caused by regulatory compliance, priorities, demand from stakeholders, cultural factors, and macroeconomics considerations. The effect of CSR on market-adjusted stock returns varies over time and create a positive and negative result depending on the period of analysis because this strategy is a long-term process. Lastly, insights into the importance of building corporate citizenship on sustainability and firm performance are elaborated.